(untitled) (Raparin Journal of Humanities (RJH), 2025)
The pedagogical importance of multimodal composing in second language (L2) writing has received significant attention from researchers in the field of English language teaching. Recently, in the L2 writing class, research on the potential of this approach to teaching writing has been the focus of many researchers. The aim of the present study is to explore EFL learners’ perceptions of incorporating Multimodal Composing (MC) into EFL writing instruction. 33 EFL learners from the English department at the University of Halabja participated in this study. A mixed methods research design was used to conduct the study. The data were collected using a reflection survey and semi-structured interviews. The quantitative data were analyzed using the Statistical Package for the Social Sciences (SPSS 27). Non-parametric statistical measures were used for the purpose of presenting and comparing learners’ perceptions across three multimodal tasks. The qualitative data collected from the semi-structured interviews were analyzed thematically using NVivo 15 to discover main patterns and themes. The results of the study revealed that EFL learners had positive perceptions of incorporating multimodal composing activities into writing instruction. Learners’ perceptions changed over time; they became more comfortable with the multimodal tasks, and their perceptions of the pedagogical importance of the tasks became increasingly positive. The majority of participants perceived the multimodal tasks as more motivating and engaging than traditional writing activities. Learners also reported that the tasks were beneficial in terms of increasing task engagement, audience awareness and improving writing skills through reviewing and revising.